Improving the modeling of couples' labour supply - Robert Breunig; Deborah A. Cobb-Clark; Xiaodong Gong (Institute for the Study of Labor (IZA), 2005)
We study the work hours of Australian couples, using a neoclassical labour-supply model in which couples choose from a small, realistic set of possible wife-husband working hour combinations We introduce three improvements to this standard model. First, we allow partners' preferences about non-market time to be correlated. We also correct the estimates to account for the fact that we estimate the non-observable wage rates of individuals who do not work. Lastly, we allow each individual's preferences for non-market time to be correlated with her or his wage rate. These changes, which substantially enhance the realism of the standard, discretized labour-supply model, also have an important impact on the results. We estimate the model using HILDA data and find wage elasticities of labour supply 0.26 for men and 0.50 for women that are twice as large as those found without these three innovations. Using simulation methods, we then analyze the expected impact of the 2005/06 Australian tax reform. As a result of the tax cuts, we expect working hours to increase by 1.7 per cent for both men and women and household after-tax incomes to increase by approximately 60 per week on average. For families with two wage earners, each earning between 25,000 and 55,000 per year, our model predicts an after-tax increase in income of 38 after accounting for these labour supply effects much larger than the Australian Government's own prediction of 12, which does not allow for labour supply effects.
Keywords: C51; D10; J22; 330; family labour supply; Australia; simulated maximum likelihood; discretized structural model; Familienökonomik; Arbeitsangebot; Familienbesteuerung; Sozialhilfe; Steuerreform; Australien